A writer’s reference : - Hacker, Diana (Bedford/St. Martin’s, 2009)
To help your students write in composition and in other college courses, A Writer's Reference with Writing in the Disciplines includes a tabbed section with advice and model papers in nine academic disciplines: biology, business, criminology, education, engineering, history, music, nursing, and psychology.